Client’s factors of working alliance: A preliminary study in Career Construction Counseling - Cardoso, Paulo (2022)
This study aims to identify the client factors that predict working alliance in career construction counselling. The sample included 49 participants (34 females). A demographic questionnaire collected information about clients’ gender, age and educational level. Distress was assessed using the Outcome Questionnaire-45. The strength of working alliance was measured by the Work Alliance Inventory-Short and Revised at the end of both the first and the last career counselling sessions. Multiple regression analyses were computed out to test whether client characteristics (gender, age, educational level and distress) predicted the strength of the working alliance. Results showed client distress and low educational level to be significant predictors of working alliance strength at both moments. Study limitations and research implications are presented. Findings suggest practices fostering working alliance, namely, boosting counsellors’ awareness of signs of client distress and working on client expectations for the career counselling process.